Covid-19 Impact on Micro and Small-Medium Enterprises Operating and Analysis of Government Stimulus Packages - Muhammad Haykal; Iswadi Bensaadi; Saifuddin Yunus (Budapest International Research and Critics University, 2022)
This study aims to compare tourists visiting, sales, investments, and innovations before and during Covid-19 and explore government stimulus packages for micro and small-medium enterprises (MSMEs). The research is a quantitative and cross-sectional study. Data was collected using a questionnaire at 120 MSMEs of the tourism sector in Aceh. One-sample t-test was used to analyze tourists visiting, sales, investments, and innovations before and during Covid_19. Frequency analysis is performed to explain MSMEs that receive the government's stimulus packages. The result shows that tourists visiting, sales, investments during Covid-19 were lower than before, and the innovations are indifferent before and during Covid_19. Using frequency analysis indicates that most MSMEs were not receiving government stimulus packages. The study contributes to the existing literature about tourists visiting, sales, investment, innovations at MSMEs, and practical implications for policymakers to support business operation sustainability during the Covid-19 crisis.